Optimal budget deficits and immigration - Karin Mayr (Johannes Kepler University of Linz, Department of Economics, 2006)
The paper shows that immigration can create an incentive for deficit-spending among natives. If immigrants use up some given share of public funds net of debt service, a policy of running budget deficits becomes optimal. The optimal budget deficits are higher, the higher the share of net public funds spent exogenously on immigrants. We take the share of immigrants in the total population as a proxy for exogenous spending on immigrants and estimate its effect on budget deficits for 20 OECD countries during 1980 - 1995. We find the effect to be significant and positive, suggesting that exogenous spending was increasing during that time.
Keywords: H62; H63; F22; 330; optimal budget deficits; immigration; tax-smoothing